Standard is to write "exponents" as "^(-1)". Although, strictly speaking, the "-1" here is not an "exponent"- sin^(-1)(x) is the inverse function, the funct, v, such that f(sin^(-)(x))= sin^(-1)(f(x))= x, not 1/sin(x).
This problem would be easy if it were just "cos(sin^(-1)(x))" because, for any u, cos(u)= sqrt(1- sin^2(u)) so that cos(sin^(-1)(x))= sqrt(1- (sin(sin^(-1)(x))^2)= sqrt(1- x^2) because, of course, sin(sin^(-1)(x))= x.
So, do you know any ways to simplify cos(a- b) into functions of a and b separately?
This site uses cookies to help personalise content, tailor your experience and to keep you logged in if you register.
By continuing to use this site, you are consenting to our use of cookies.